Tethered IL15-IL15Rα augments antitumor activity of CD19 CAR-T cells but displays long-term toxicity in an immunocompetent lymphoma mouse model - Felipe Prosper; Sandra Hervás-Stubbs; Juan Jose Lasarte; Noelia Casares; Teresa Lozano; Celia Martín-Otal; Aritz Lasarte-Cia; Flor Navarro; Inés Sánchez-Moreno; Marta Gorraiz; Patricia Sarrión; Juan Roberto Rodriguez-Madoz; et al. (Journal for ImmunoTherapy of Cancer)
Background Adoptive cell therapy using genetically modified T cells to express chimeric antigen receptors (CAR-T) has shown encouraging results, particularly in certain blood cancers. Nevertheless, over 40% of B cell malignancy patients experience a relapse after CAR-T therapy, likely due to inadequate persistence of the modified T cells in the body. IL15, known for its pro-survival and proliferative properties, has been suggested for incorporation into the fourth generation of CAR-T cells to enhance their persistence. However, the potential systemic toxicity associated with this cytokine warrants further evaluation.Methods We analyzed the persistence, antitumor efficacy and potential toxicity of anti-mouse CD19 CAR-T cells which express a membrane-bound IL15-IL15Rα chimeric protein (CD19/mbIL15q CAR-T), in BALB/c mice challenged with A20 tumor cells as well as in NSG mice.Results Conventional CD19 CAR-T cells showed low persistence and poor efficacy in BALB/c mice treated with mild lymphodepletion regimens (total body irradiation (TBI) of 1 Gy). CD19/mbIL15q CAR-T exhibits prolonged persistence and enhanced in vivo efficacy, effectively eliminating established A20 B cell lymphoma. However, this CD19/mbIL15q CAR-T displays important long-term toxicities, with marked splenomegaly, weight loss, transaminase elevations, and significant inflammatory findings in some tissues. Mice survival is highly compromised after CD19/mbIL15q CAR-T cell transfer, particularly if a high TBI regimen is applied before CAR-T cell transfer.Conclusion Tethered IL15-IL15Rα augments the antitumor activity of CD19 CAR-T cells but displays long-term toxicity in immunocompetent mice. Inducible systems to regulate IL15-IL15Rα expression could be considered to control this toxicity.